Educational resilience in dropouts who return to gain high school degrees - Wayman, Jeffrey C., author; Cobb, R. Brian, advisor; Mantle-Bromley, Corrine, committee member; Swaim, Randall, committee member; Timpson, W. M., committee member (Colorado State University. Libraries, 2000)
This study examined school dropouts of Mexican American and non-Latino white ancestry who have gained high school diplomas, GEDs, or neither, identifying factors that are associated with dropouts' attainment of high school credentials. This work broadened the knowledge base surrounding returning dropouts by considering the returning dropout an educationally resilient student. Personal and environmental factors from the study of educational resilience were considered, along with factors shown by previous research to distinguish returning dropouts with degrees from dropouts with no degrees. The study encompassed the entire dropout population, including participants who had dropped out as early as 7th grade and utilizing multiple imputation to account for missing data due to participants who were not present in the second wave of data collection. Logistic regression analyses were performed to identify a parsimonious set of factors which distinguished dropouts who held degrees (diploma or GED) from those who did not. Similar analyses were performed to distinguish participants who had attained diplomas from those who had attained GEDs. It was estimated that 59.2% of dropouts return to obtain high school credentials. School capability, age at dropout, perception of school success, and friends in school significantly predicted degree attainment, while school capability, grade at dropout, self-confidence and educational aspirations significantly predicted the type of degree held. These relationships did not vary by ethnicity, although degree attainment was less likely for Mexican American dropouts. The study concludes that consideration of factors from the study of educational resilience significantly adds to previous knowledge of return factors, and that although degree decisions are partially a function of factors which are relatively intractable at the high school level, they are also a function of factors which can be influenced at the high school level. Building resilience in potential dropouts can be an effective method for promoting degree attainment, and schools and educators may be able to play a role in the building of such resilience.
Keywords: secondary education; vocational education; teacher education; minority and ethnic groups; sociology